2020
DOI: 10.3390/bios10120198
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Approaches to Improve the Sensitivity of Lateral Flow Immunoassay of the Antibiotic Lincomycin

Abstract: This study provides a comparative assessment of the various nanodispersed markers and related detection techniques used in the immunochromatographic detection of an antibiotic lincomycin (LIN). Improving the sensitivity of the competitive lateral flow immunoassay is important, given the increasing demands for the monitoring of chemical contaminants in food. Gold nanoparticles (AuNPs) and CdSe/ZnS quantum dots (QDs) were used for the development and comparison of three approaches for the lateral flow immunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, the low versatility of the latex nanoparticles inhibits the development of further strategies to combine the strip with transducers. To enhance the sensitivity, the traditional AuNPs label has been replaced by an AuNP nanocomposite and novel nanoparticle, including AuNP-decorated silica nanorods, quantum dots, fluorescence-quenching, and particles used in other emerging detection principles such as magnetic systems [67]. For example, Lu et al reported two chromatographic immunoassays to detect Stx, using the signal la-bels colloidal AuNPs and CdTe QDs, respectively, to reduce the detection limit [68].…”
Section: Lateral Flow Immunoassaysmentioning
confidence: 99%
“…In addition, the low versatility of the latex nanoparticles inhibits the development of further strategies to combine the strip with transducers. To enhance the sensitivity, the traditional AuNPs label has been replaced by an AuNP nanocomposite and novel nanoparticle, including AuNP-decorated silica nanorods, quantum dots, fluorescence-quenching, and particles used in other emerging detection principles such as magnetic systems [67]. For example, Lu et al reported two chromatographic immunoassays to detect Stx, using the signal la-bels colloidal AuNPs and CdTe QDs, respectively, to reduce the detection limit [68].…”
Section: Lateral Flow Immunoassaysmentioning
confidence: 99%
“…Despite the signi cant advantages of sensitivity and selectivity, these techniques are time-consuming, labour-intensive, and expensive to operate due to the need for specialized equipment, extensive pre-treatment, and high operating costs. As a result, these methods are di cult to devise for on-site monitoring of FQs (Serebrennikova et al 2020). Fluorescence detection thus offers a substitute for high selectivity, sensitivity, and accuracy, as well as low cost, quick and easy operation for detection of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is a sensitive molecular spectral technique. Generally, the nanostructured substrates functionalize with Raman reporter molecules, and strong characteristic peaks are generated in the SERS spectrum, thus achieving quantitative detection of the analyte [10]. SERS substrates usually include gold, silver, and other noble metal materials, and the signal intensity of SERS can be effectively enhanced by improving the substrate [11].…”
Section: Introductionmentioning
confidence: 99%